Ensaio clínico pragmático e randomizado da eficiência da ceftriaxona versus cefazolina na prevenção de bacteriúria e infecções pós-operatórias em cirurgia de ressecção transuretral da próstata - Mandim, Beatriz Lemos da Silva (2014)
PURPOSE: Surgical site infections and urinary tract infections cause great morbidity in postoperative patients undergoing urological surgery. Bacterial resistance and misuse of antimicrobial drugs are great concern nowadays. Transurethral resection of the prostate (TURP) is a surgical procedure indicated for the treatment of benign prostatic hypertrophy (BPH). Most studies that evaluate the efficacy of antimicrobial prophylaxis, exclude patients at risk. Broad-spectrum antimicrobials should be reserved for special cases, where the risk or resistant organisms are present. We investigated whether single-dose intravenous ceftriaxone, thirty minutes before surgery, would decrease infections like bacteriuria and sepsis and compared to cefazolin, in TURP patients, with short-term removal of indwelling urethral catheter at discharge, their evaluation during 30 days and predictive correlations of infectious complications in these patients. METHODS: Pragmatic, prospective, double-blind trial, 130 patients were randomly assigned to receive a single dose of either ceftriaxone 2g IV (66 subjects) or cefazolin 2g IV (64 subjects), thirty minutes prior to surgery. They were assessed at hospital discharge, and seven and thirty days postoperatively. We evaluated ASA, urinary catheter prior to surgery, urological risk factors, prostate size, and duration of surgery. Cultures of urine and prostatic tissue were used as a baseline. The outcomes considered as infection were: asymptomatic bacteriuria, UTI, prostatites, epididimites and sepsis, 30 days postoperatively. RESULTS: Ceftriaxone did show superiority to cefazolin, but was not significant (OR 0.567, 95% CI [0.234 to 1.414], p = 0.228), in the prevention of infections for patients undergoing TURP. Among the covariates, only urological risk factors had statistical significance. Sub-analysis considering patients without bacteriuria at baseline demonstrated a potential prophylactic effect of ceftriaxone in relation to cefazolin, but, once again, it was not statistically significant (adjusted odds ratio = 0.492 95% CI 0.130 to 1.863] p = 0.297). There were no cases of septicemia. Sub analyses considering patients without bacteriuria at baseline, demonstrated a potential prophylactic effect of ceftriaxone in relation to cefazolin, but, once again, not statistically significant (adjusted odds ratio = 0.492 95% CI 0.130 to 1.863] p = 0.297). There were no cases of septicemia. CONCLUSIONS: A single dose of ceftriaxone was similar to cefazolin in the prevention of postoperative infections in patients undergoing TURP who had early postoperative removal of indwelling catheters. Preoperative evaluation should include routine urine culture to determine infectious status and guide treatment of patients through the antibiogram.